Quantification of Fat Mobilization in Patients Undergoing Coronary Artery Revascularization Using Off-pump and On-pump Techniques - Ajzan, Ahmed (J Extra Corpor Technol, 2006)
Fat mobilization during cardiopulmonary bypass (CPB) is a recognized risk of the procedure. Intravascular mobilization of fat emboli subsequent to CPB has been implicated in some of its recognized pathophysiologies, particularly with regard to cerebral embolic injury. The aim of this study was to investigate whether fat mobilization is still a real issue in modern perfusion practice and to determine whether off pump coronary artery bypass techniques minimize this risk. Thirty patients undergoing routine elective coronary artery bypass graft (CABG) surgery were divided into two groups. Group 1 patients underwent off pump coronary artery bypass (OPCAB) procedures, and group 2 underwent CABG supported with CPB. Blood samples were taken from the CPB patients at the beginning, middle, and end of the procedure, from the suction line, from the arterial line, and from the venous line for measurement of fat emboli present. Samples were taken at corresponding time-points from the OPCAB patients for similar measurements. Fat emboli were counted manually using Oil red O staining and light microscopy. The fat emboli were sized using calibrated microspheres as a visual size contrast. No fat emboli were observed in any of the blood samples taken from the OPCAB patients. There were fat emboli present in all samples taken during CPB from all sources. The count was highest in the suction system and lowest in the venous blood and tended to increase during CPB. There was an absence of large fat emboli in the venous blood, which tends to indicate that the larger fat emboli lodge in the microvasculature. OPCAB surgery eliminates the risk of fat embolization in patients undergoing coronary revascularization. The suction system is the major source of fat emboli during CPB, and despite the multiple filtration components of the CPB system, fat emboli of various and significant sizes do reach the patient. Fat embolization remains a risk in routine elective CABG surgery. Cardiotomy suction should be eliminated where possible.